Complications after polydioxanone threads (PDO) for facial lifting - a literature review - Lewandowska, Karina; Staniszewska, Izabela; Baran, Milena; Turczynowicz, Magda; Retman, Patrycja (Journal of Education, Health and Sport, 2024)
Introduction: The popularity of cosmetic treatments is increasing, including treatments using polydioxanone (PDO) threads. Among the various complications that PDO threads can cause are swelling, skin dimpling, paresthesia, thread visibility/palpability, infection, and thread extrusion. On the other hand, it is an alternative to surgical facelift. Purpose of work: To collect information on the complications after PDO threads for facial lifting. Summary: In the literature review, there were reported complications after PDO threads for facial lifting as edema, allergy, inflammation, infection, skin dimpling, contour irregularity, visible threads, hematoma, thread extrusion, and incomplete facial paralysis. Knowledge of complications after face lifting with PDO threads allows us to prepare for these side effects and act appropriately in the event of their occurrence, thus avoiding the long-term effects of the cosmetic procedure.